IMPLEMENTATION OF FISCAL DECENTRALIZATION IN INDONESIA: 2001-2009 - Nursini, Nursini (Universitas Muhammdaiyah Surakarta, 2012)
In Indonesia, the implementation of fiscal decentralization has entered the 9th year, however, so far many problems and obstacles which is faced during the implementation to stimulate economic growth and reduce poverty. This study aims to analyze: trend of government expenditure in decentralization era and regional autonomy during 2001-2009 and fiscal decentralization degree in Indonesia. This objective is achieved through descriptive analysis using secondary data for 2001-2009. The result shows central government expenditure tends to decreased and transfer expenditure increased significantly every year in absolutely, but annual growth rate fluctuated considerably. This indicates the allocation portion of the transfers was unstable. The largest component of transfers is fund balance and tends to increase every year significantly, fiscal decentralization degree at districts/city and province increased in 2007-2008. It is recommended to regional government to allocate public interest bigger than for government administration such as personnel government spending.